Smart Stimuli-responsive Nanogels: A Potential Tool for Targeted Drug Delivery - Dhanawat, Meenakshi; Garima; Wilson, Kashish; Bhushan, Bharat; Chalotra, Rishabh; Gupta, Sumeet; Chaubey, Pramila (Current Pharmaceutical Design, 2025)
Nanogels (NGs) are presently the focus of extensive research because of their special qualities, including minimal particle size, excellent encapsulating efficacy, and minimizing the breakdown of active compounds. As a result, NGs are great candidates for drug delivery systems. Cross-linked nanoparticles (NPs) called stimulus-responsive NGs are comprised of synthetic, natural, or a combination of natural and synthetic polymers. These NPs can swell in response to large amounts of solvent, but their structural makeup prevents them from dissolving. Furthermore, in response to (i) physical stimuli like temperatures, ion strength, and magnetized or electrical fields; (ii) chemical stimuli like the pH level, molecules, or ions; (iii) biological stimuli like the enzymatic substrate or affinity ligand, they transform into a hard particle (collapsed form) from a polymer solution (swell form). Over the past decade, there has been a major advancement in the creation of “smart” NGs in applications related to therapeutics and diagnosis, involving nucleic acid and intracellular drug delivery, photodynamic/photothermal treatment, biological imaging, and its detection. The nanogels reviewed in this article rely only on temperatures, pH, light, magnetic fields, and combinations of those variables. Developing a targeted delivery vehicle will greatly benefit from the presented information, especially when used for Core-shell multi-sensitive photo-sensitive nanogels.
Keywords: nanogels